The response of root system architecture to soil compaction - Tracy, Saoirse (2013)
Soil compaction has been described as the most serious environmental problem caused by conventional agriculture, as it results in several stresses which may interact simultaneously, including increased soil strength, decreased aeration and reduced hydraulic conductivity. Root system architecture (RSA) is the arrangement of roots within the soil matrix and is important because the specific deployment of roots within the soil can determine soil exploration and resource uptake. As roots deliver water and nutrients to growing plants, whilst also providing anchorage, their importance cannot be overstated. Yet, our understanding of how roots interact with the surrounding soil, especially at the micro-scale level, remains limited because soil is an opaque medium, so preventing roots from being visualised without disturbing them. Destructive techniques are commonly employed for the analysis of RSA, however this can result in the loss of key information concerning root architecture, such as elongation rates and root angles and important soil characteristics such as soil structure and pore connectivity. However, X-ray Computed Tomography (CT) has been shown to be a promising technique for visualising RSA in an undisturbed manner. The species considered in this thesis were wheat (Triticum aestivum L.) and tomato (Solanum lycopersicum L.). Further information regarding the response of roots to soil compaction has been achieved through the use of X-ray CT, automatic root tracing software and novel image analysis procedures. Soil compaction significantly affected root length, volume, surface area, angle, diameter, elongation rates and root path tortuosity, however the influence of soil texture on root responses to soil compaction was significant. Moderate compaction benefits root growth in clay soil, possibly due to the greater nutrient and water holding capacity, but adversely affected root growth in loamy sand. The results suggest that there is an optimum level of soil compaction for the different soil types. Roots elongated rapidly between 2-3 days after germination (DAG), it is hypothesised that is related to the mobilization of seed storage substances to the growing roots. The use of transgenic mutants of tomato with altered levels of abscisic acid (ABA) has provided a greater insight into the role of ABA in mediating root responses to soil compaction. This work will enable better phenotyping of plant varieties with enhanced root system traits for resource foraging and uptake. Knowledge of the responses of root systems in heterogeneous soil is vital to validate root phenotypes and overcome future food security challenges.